The Potential of Chitosan-Starch Blend Polymers as Edible Coatings for The Preservation of Fruits and Vegetables: A Mini-Review - Fadli Hafizulhaq; Putri Wulandari Zainal; Sharifah Hanis Yasmin Sayid Abdullah (Green Engineering Society, 2023)
Fruits and vegetables are essential for human life. Maintaining the quality and safety of fruits and vegetables are critical challenges for the food packaging industry in this decade. Chitosan and starch are most widely used for food packaging as they bring unique properties for packaging applications. Chitosan has good antimicrobial properties but weak water vapor permeability. Meanwhile, starch has a better water vapor barrier but has poor mechanical properties. This paper discusses the application of chitosan and starch blends in the field of films and coatings. Several characteristics, such as mechanical, thermal, antimicrobial properties, solubility, and water vapor permeability, are also discussed. This review also discussed several applications of chitosan-starch-based films and coatings for the preservation of fruits and vegetables.